Tanggung Jawab Pemerintah Provinsi Nusa Tenggara Timur dalam Pembangunan Infrastruktur Jalan Berdasarkan Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah: Studi pada Ruas Jalan Dangka Mangkang–Benteng Jawa–Dampek - Sergius Fantura Feriyanto; Josef Mario Monteiro; Agnes Doortji Rema (Student Scientific Creativity Journal, 2026)
Road infrastructure plays a vital role in supporting economic, social, and cultural activities. This study examines the implementation of the East Nusa Tenggara Provincial Government’s authority in developing the Simpang Dangka Mangkang–Benteng Jawa–Dampek road, a 50.83 km strategic route connecting three sub-districts in East Manggarai Regency. Although the road has been placed under provincial authority through Governor’s Decree No. 403/KEP/HK/2023, several sections remain severely damaged. This research employs an empirical legal (socio-legal) method with a conceptual approach. Data were collected through interviews, field observations, documentation, and the examination of primary, secondary, and tertiary legal materials. Data were analyzed using descriptive qualitative methods to compare legal provisions (das Sollen) with their implementation in practice (das Sein). The findings indicate that the Provincial Government, through the Public Works and Spatial Planning Agency (PUPR), has carried out its responsibilities in planning, implementation, supervision, and maintenance in stages. However, these efforts have not been fully effective, as damaged road sections persist and legislative oversight remains limited due to insufficient transparency in the road status transfer process. Key challenges include budget constraints, limited technical personnel, inadequate infrastructure, difficult geographical conditions, extreme weather, and weak coordination among provincial and district governments and local communities.